2019
DOI: 10.15252/emmm.201810204
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of simultaneous VEGF ‐A/ ANG ‐2 neutralization in suppressing spontaneous choroidal neovascularization

Abstract: This study independently confirms in vivo in the JR 5558 mouse model of aberrant retinal angiogenesis, that simultaneous VEGF ‐A and ANG ‐2 neutralization using a bispecific anti‐ VEGF ‐A/ ANG ‐2 antibody reduces vascular leakage, immune reactivity and apoptosis more effectively than either agent alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 8 publications
(11 reference statements)
2
45
0
1
Order By: Relevance
“…Initial studies showed that vitreous levels of Ang-2 are elevated in nAMD, diabetic retinopathy (i.e., DME), and retinal vein occlusion [ 19 , 61 , 62 ]. In animal studies, spontaneous choroidal neovascularization models show faricimab and other VEGF-A/Tie-2 targeting agents reduce vessel lesions and neuron loss, inhibit retinal leukocyte infiltration, and prolong the anti-leakage effect [ 62 , 63 ]. Preclinical studies showed that blocking Ang-2 reduces VEGF-induced endothelial barrier breakdown [ 62 , 64 ].…”
Section: Clinical Studies Of Faricimab In Diabetic Macular Edemamentioning
confidence: 99%
“…Initial studies showed that vitreous levels of Ang-2 are elevated in nAMD, diabetic retinopathy (i.e., DME), and retinal vein occlusion [ 19 , 61 , 62 ]. In animal studies, spontaneous choroidal neovascularization models show faricimab and other VEGF-A/Tie-2 targeting agents reduce vessel lesions and neuron loss, inhibit retinal leukocyte infiltration, and prolong the anti-leakage effect [ 62 , 63 ]. Preclinical studies showed that blocking Ang-2 reduces VEGF-induced endothelial barrier breakdown [ 62 , 64 ].…”
Section: Clinical Studies Of Faricimab In Diabetic Macular Edemamentioning
confidence: 99%
“…In July 2017, the journal issued an editorial expression of concern (https://doi.org/10.15252/emmm.201707895) to alert readers that the data in Figs 4 and 5 needed further analysis and verification. Researchers at Roche have since confirmed in an independent study based on independently obtained data that the conclusions from these figures are valid (Foxton et al , ).…”
mentioning
confidence: 88%
“…Due to its additional role in inflammation that is implicated in wet AMD, ANG2 has become a potential therapeutic target in wet AMD beyond anti-VEGF therapies (Gahn and Khanani, 2018). In vivo experiments have recently demonstrated ANG2 and VEGF combinatory inhibition led to reduced neovascular lesion formation in a spontaneous chronic choroidal neovascularization mouse model (JR5558 mice) (Foxton et al, 2019). This has been carried forward to phase 1 and 2 clinical trials with the bispecific antibody anti-VEGF-A/ANG2 (RG7116; Roche/Genetech).…”
Section: Vascular Mechanisms In Choroidal Neovascularizationmentioning
confidence: 99%